Educational Marketing Management Strategy to Increase the Number of New Students - Ilyas Arizka; Duwi Habsari Mutamimah; Asis Sustiawan (Journal of Research in Social Science and Humanities, 2026)
This study aims to analyze effective educational marketing management strategies in increasing the number of new students at Mts Ma'arif 11 Tokawi. In an era of increasingly fierce competition, madrasas are required to implement appropriate marketing strategies in order to attract the interest of prospective new students and parents. This study uses a qualitative approach with a case study method on madrasas that have succeeded in increasing the number of new students. Data collection techniques are carried out through in-depth interviews, observation, and documentation. The results of the study indicate that the marketing strategies used include: (1) planning excellence as a promotion that will be used to attract the interest of prospective new students, (2) organizing the formation of a new student admissions committee, (3) implementing strategies that have been determined by the madrasa such as promoting madrasa activities through social media and socialization to the community, (4) monitoring and evaluation are carried out through internal meetings with the PPDB committee led directly by the principal of the madrasa by reviewing the results of the marketing strategies that have been implemented in terms of the level of community response, the effectiveness of the use of social media and the number of prospective new students who register. The implementation of this marketing strategy has been proven to increase the attractiveness of madrasahs and result in an increase in the number of new students. This research is expected to provide practical recommendations for madrasah administrators in designing adaptive and sustainable marketing strategies.